PERENCANAAN PENGENTASAN KEMISKINAN MELALUI DANA DESA (DD) DI DESA AMASARA KECAMATAN BAITO KABUPATEN KONAWE SELATAN - Herwan Malengga; La Ode Geo; Muh. Natsir (Universitas Halu Oleo, 2020)
This study aims to analyze: 1) Poverty level in Amasara Village, Baito District, South Konawe Regency; 2) Influence between poverty levels and village funds (DD) in Amasara Village, Baito District, South Konawe Regency; 3) Factors that influence the causes of poverty in Amasara Village, Baito District, South Konawe Regency; and 4) Poverty alleviation plan in Amasara Village, Baito District, South Konawe Regency. The study uses quantitative and qualitative approaches. The sample (informants) of the study were 39 people who were determined purposively.The data analysis technique in the study was carried out quantitatively, 0.6 eview multiple linear regression and ordinary least squares (OLS) and qualitative descriptive analysis. The results showed that the poverty level in Amasara Village, Baito District, South Konawe Regency was at a moderate level, meaning that poverty could still be done by alleviation through various plans for policy and program approaches. In aggregate, poverty in Amasara Village, Baito District, Konawe Selatan District has a significant effect on the allocation of village funds (DD) of 87.99%.Partially, the allocation of village funds through the construction of facilities and infrastructure and community empowerment has a significant effect on poverty in Amasara Village, while the allocation of village funds (DD) for community development does not significantly influence poverty in Amasara Village. The main factors that influence the causes of poverty in Amasara Village, Baito District, Konawe Selatan District are; a) Low land ownership; b) Limited capital access; and c) Basic needs are limited. Poverty in Amasara Village is also supported by factors; a) Low education; b) Unemployment; c) Still traditional economic management; and d) Culture of saving that has not been developed. The poverty alleviation plan in Amasara Village, Baito Subdistrict, Konawe Selatan District for a short scale (priority) is: a) Hold entrepreneurial education and training and the like; b) Providing / facilitating the formation of new employment opportunities through capital assistance; c) Providing creative venture capital and business development assistance; d) Providing assistance for basic household needs that have not received food assistance and others from the central government; and e) Counseling (community development) and facilitating community financial management by saving money. While the long-term plan is a) Provision of business areas (temporary rights or property rights) for agricultural or plantation activities; and b) Counseling (guidance) on community financial management.Keywords: Poverty and Village Funds